Power electronic converters and systems : frontiers and applications - Trzynadlowski, Andrzej (IET power and energy series ;, 2015)
The book is written at postgraduate level and comprises N chapters dealing with the following subjects: semiconductor power devices; multilevel converters; multi-input converters; modular converters; matrix converters; soft-switching converters; Z-source converters; switching power supplies; smart power electronic modules; permanent magnet synchronous motor drives; induction motor drives; wind energy systems; photovoltaic energy systems; automotive energy systems; shipboard power systems; power grid; distribution generation; microgrids; uninterruptible power supplies; wireless power transfer; and power electronics system control.